PENGARUH E-SERVICE QUALITY ( SIAKAD CLOUD) TERHADAP KEPUASAN MAHASISWA STIA YPPT PRIATIM TASIKMALAYA - Iis Miati; Rudi Setiawan (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
Education is one of the efforts to achieve a standard of living or for better progress. Each university will provide good services to attract prospective students (students), apart from providing supporting and adequate facilities and infrastructure, and competent human resources in their fields. At this time a service can be done directly or indirectly. Electronic Services System or Electronic Services which is abbreviated as E-Services is a leading application that utilizes Information and Communication Technology. The web-based Academic Information System (SIAKAD CLOUD) aims to make it easier for students and lecturers to obtain the information they need, such as lecture materials, lecture schedules, Mid-semester Examination Schedules, Semester Final Exams and other campus activity information. The author uses an associative research type with a quantitative approach, while the number of samples in this study is 136 students of STIA YPPT Priatim Tasikmalaya. The results of the research and discussion show that the value of R Square or the square of the value of R, obtained a value of 0.537 or 53.7%, which means that community satisfaction is influenced by the existence of E-Service Quality of 53.7%. The significance value is 0.000, which means it is far from the alpha value, which is 0.05 (5%), meaning that E-Service Quality has an influence on student satisfaction.